Challenges of Applying Artificial Intelligence Systems in the Faculties of Sports Sciences in Jordanian Universities from the viewpoint of Faculty Members - Al-Hwayan, Eman (Dirasat: Educational Sciences, 2024)
Objectives: The study aims to identify the challenges facing the application of artificial intelligence systems in the faculties of Sports Sciences in Jordanian universities from the viewpoint of faculty members. Methods: The study adopted the descriptive survey approach, and the study sample consisted of (80) faculty members who study in Jordanian public universities in Jordanian universities. To achieve the objectives of the study, the study tool was prepared, a questionnaire consisting of (23) items that measure the challenges of applying artificial intelligence systems in the faculties of sports sciences in Jordanian universities. Results: The results showed that the study sample’s estimation of the challenges of applying artificial intelligence systems in the faculties of sports sciences at Jordanian universities for the two axes: (material challenges and legislative challenges) was high. For the two axes: (human challenges and technical challenges), the estimation degree was moderate. The results also indicated that there were no statistically significant differences at the level of significance (α ≤ 0.05) regarding the total degree of challenges in applying artificial intelligence systems attributed to years of experience. Significant differences were found in estimating material challenges based on academic rank, favoring associate professors and professors. Conclusions: The study recommends the enactment of specific legislation on artificial intelligence in partnership with experts and compliance with legal requirements during programming and development of applications to mitigate their risks. It recommended enhancing the financial allocation for scientific research in the field of artificial intelligence and its applications in the field of sports science.